Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s43393-022-00151-2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted osmotic dehydration, followed by convective drying of papaya: effect on physicochemical and functional quality parameters

Abstract: Papaya is a rich source of nutrients, antioxidants, and vitamins; however, it is highly perishable and hence needs to be preserved using suitable unit operations. Drying is an economical method of papaya treatment, but results in the loss of essential nutrients and also degrades its pigments, color, and texture. Therefore, this work aims to utilize ultrasound and osmotic dehydration as pretreatment strategies to preserve the rich composition of papaya during conventional hot air drying. The dried papaya slices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Another study by Yilmaz et al (2019) reported that the yield of β-carotene content from carrot slices increased from 59.251 mg/100 g (dry matter) to 99.837 mg/100 g (dry matter) after they were pretreated with US before extraction. US treatment when used as a pretreatment on carrots enhanced the extraction and release of carotenoids from the cellular matrix of the tissue (Chandra et al, 2022). The mechanical waves and cavitation generated by US can disrupt the cell walls and cellular structure, promoting the release of carotenoids that are typically trapped within the cells (Rahaman et al, 2019).…”
Section: Total Carotenoid Contentmentioning
confidence: 99%
“…Another study by Yilmaz et al (2019) reported that the yield of β-carotene content from carrot slices increased from 59.251 mg/100 g (dry matter) to 99.837 mg/100 g (dry matter) after they were pretreated with US before extraction. US treatment when used as a pretreatment on carrots enhanced the extraction and release of carotenoids from the cellular matrix of the tissue (Chandra et al, 2022). The mechanical waves and cavitation generated by US can disrupt the cell walls and cellular structure, promoting the release of carotenoids that are typically trapped within the cells (Rahaman et al, 2019).…”
Section: Total Carotenoid Contentmentioning
confidence: 99%